2006
DOI: 10.1002/marc.200600031
|View full text |Cite
|
Sign up to set email alerts
|

Salt‐Induced Depression of Lower Critical Solution Temperature in a Surface‐Grafted Neutral Thermoresponsive Polymer

Abstract: Summary: Quartz crystal microbalance with dissipation monitoring (QCM‐D) is employed to determine the effect of salt on the volume phase transition of thermoresponsive polymer brushes. Changes in mass and viscoelasticity of poly(N‐isopropylacrylamide) (PNIPAM) layers grafted from a QCM‐D crystal are measured as a function of temperature, upon contact with aqueous solutions of varying salt concentrations. The phase‐transition temperature of PNIPAM brushes, TC,graft, quantified from the QCM‐D measurements is fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 27 publications
2
67
1
Order By: Relevance
“…The temperature-induced wettability variation has been confirmed by several groups on systems involving surface-grafted PNIPAAm. In a recent paper from the authors' laboratory, some studies are summarised that demonstrate the coil-to-globule transition in surface-grafted PNIPAAm is affected by the presence of salt (Jhon et al 2006). The latter effect may be particularly important when considering application of PNIPAAm-based smart coatings in salty waters (e.g.…”
Section: Superhydrophobicity and Marine Fouling 349mentioning
confidence: 96%
“…The temperature-induced wettability variation has been confirmed by several groups on systems involving surface-grafted PNIPAAm. In a recent paper from the authors' laboratory, some studies are summarised that demonstrate the coil-to-globule transition in surface-grafted PNIPAAm is affected by the presence of salt (Jhon et al 2006). The latter effect may be particularly important when considering application of PNIPAAm-based smart coatings in salty waters (e.g.…”
Section: Superhydrophobicity and Marine Fouling 349mentioning
confidence: 96%
“…Another important consideration when studying these gels is the effect of salt on the LCST of the polymers. Jhon et al studied this effect with PNIPAAm brushes and found salt to lower the LCST due to the Hofmeister effect of salt on the structure of water molecules [74].…”
Section: Hydrogelsmentioning
confidence: 99%
“…[6] In principle, such a technique can detect the adsorption, conformation and interactions of macromolecules at interface. [7][8][9][10][11][12][13][14] This short review deals with the QCM-D studies on conformational change of polymer chains. Due to the limited space, we intend to mainly review what has been done in this laboratory though other research groups have done excellent work in this field.…”
Section: Introductionmentioning
confidence: 99%